Dog10K: an international sequencing effort to advance studies of canine domestication, phenotypes and health. Issue 4 (10th April 2019) - Ostrander, Elaine A; Wang, Guo-Dong; Larson, Greger; vonHoldt, Bridgett M; Davis, Brian W; Jagannathan, Vidhya; Hitte, Christophe; Wayne, Robert K; Zhang, Ya-Ping; ,
ABSTRACT: Dogs are the most phenotypically diverse mammalian species, and they possess more known heritable disorders than any other non-human mammal. Efforts to catalog and characterize genetic variation across well-chosen populations of canines are necessary to advance our understanding of their evolutionary history and genetic architecture. To date, no organized effort has been undertaken to sequence the world's canid populations. The Dog10K Consortium (http://www.dog10kgenomes.org ) is an international collaboration of researchers from across the globe who will generate 20× whole genomes from 10 000 canids in 5 years. This effort will capture the genetic diversity that underlies the phenotypic and geographical variability of modern canids worldwide. Breeds, village dogs, niche populations and extended pedigrees are currently being sequenced, and de novo assemblies of multiple canids are being constructed. This unprecedented dataset will address the genetic underpinnings of domestication, breed formation, aging, behavior and morphological variation. More generally, this effort will advance our understanding of human and canine health.